Searching for biomolecules on Mars: Considerations for Operation of a Life Marker Chip instrument - Sephton,MA; Sims,MR; Court,RW; Luong,D; Cullen,DC (Planetary and Space Science, 2013)
The search for life on Mars requires instruments that detect organic matter and discriminate between potential sources. One such instrument is the Life Marker Chip that recognizes small molecules which are characteristic of particular organic provenances. The use of an antibody-based detection system requires the delivery of small organic compounds in a suitable solvent. Dedicated extraction protocols have been developed partly through the use of a Life Marker Chip breadboard system. Techniques which provide the strong diagnostic potential of the Life Marker Chip necessitate specific extraction protocols and appropriate sample types. Clay mineral-rich rocks are attractive targets owing to their i) association with liquid water, ii) propensity for organic matter and clay mineral co-deposition following transport from a wide hinterland, and iii) relatively large surface area and therefore potential for trapping/adsorption of organic materials. The most appropriate target organic compounds are the hydrocarbon-dominated lipids that can be highly diagnostic and have relatively high preservation potentials. The sample sites on Mars and sample preparation steps that are needed for successful detection require careful consideration. In this paper we explore the scientific results that may be obtained through the operation of a Life Marker Chip instrument on Mars.